Understanding and improving disability training for health workers in sub-Saharan Africa - Rotenberg, SH (2023)
The World Health Organization estimates that 16% of the world’s population is disabled. Health worker training in many countries has been described as limited, ineffective, and unsystematic with regard to disability. This insufficiency is likely to be detrimental to the quality of health care that disabled people receive across health systems globally and understanding the training and other mechanisms that help health workers to improve their care for disabled patients could improve health outcomes.